Effect of the ski jump bucket angle on the scour hole downstream of a converging stepped spillway - Sá Machado, L. (2020)
The present study is devoted to the analysis of scour downstream of a converging stepped spillway equipped with a ski jump bucket. The energy dissipated by jets leaving the spillway can be divided in two parts: one is the kinetic energy dissipated along the jet trajectory and another one is the energy dissipated on the impact with the tailwater. Due to the jet impact, the riverbed is subjected to turbulent pressure fluctuations resulting in the formation of a scour hole. Different experimental conditions allowed to analyse the influence of different variables on the configuration of the loose bed scour, namely: the tailwater depth, the flow rate and the exit angle of the ski jump bucket. The results were compared to those presented by other authors. For some specific flow conditions, the 3D configuration of the scour hole was also determined.